Comparison of Motion Control Screening Test Scores in Active Women With a History of Knee and Ankle Injuries - Maryam Golmoradi Marani; Amir Letafatkar; Seyed Sadredin Shojaedin (Islamic Azad University, Hamedan Branch, 2021)
Objective: Commenting on the return to sport after some injury is in doubt. The aim of this study was to investigate the relationship between test scores of movement control and a history of knee and ankle injury in active females. Methods: Statistical population of this study was 57 active females (22 healthy subjects, 19 subjects with a history of previous knee injury and 16 subjects with a history of previous ankle injury) with age ranging from 18 to 25 years old. In order to evaluate subjects, were used to the movement control test set consists of nine separate questions. Total maximum points in the subtests were 40 points, which less point was a better result in these tests. For statistical analysis, Kolmogorov-Smirnov test, Levene test, analysis of variance (ANOVA) and Tukey test were used (Significant at 95% and the alpha less than or equal 0.05, and using of the SPSS software v. 22). Results: The results of this study showed test scores of movement control earned by females with a history of ankle and knee injuries was significantly different with the healthy females (P=0.001).Compare scores of subjects with contact and non-contact injuries with healthy women showed that contact injury had higher scores than those who are non-contact injuries. The differences between the groups with any of these injuries are significant with no injury group (P=0.001).Cut-off point for this test was about 15.5. Conclusion: The scores of functional movement screening give a detailed model of the injury prevention to coaches in order to predict the risk of lower extremity injuries in athletes. So its need to coaches in order to the prevention of sports injuries, use the functional movement screening tests. To measure the performance level of the athletes before the start of the season, in order to identified athletes that are at risk of injury, in order to improve their capabilities.